A rare etiology of pulmonary nodules. (2021) - Rupal, Arashdeep; Singh, Harpreet; Jani, Chinmay; Al Omari, Omar; Patel, Dipesh; Perry, John; Thomson, Carey C.
Abstract: Introduction: Pulmonary nodules are a frequent finding on chest imaging studies, with differential including multiple benign entities, but malignancy is often also a concern. Computed Tomography (CT) and Fluorodeoxyglucose (FDG)-Positron Emission Tomography (PET) scans have improved the characterization of pulmonary nodules. However, many nodules remain indeterminate and require periodic monitoring. Here we report two nodular pulmonary amyloidosis cases as a rare etiology of enlarging pulmonary nodules with FDG avidity. Case presentation: Case 1: 75-year-old woman with a history of asthma, emphysema, bronchiectasis, and a 48 pack-year smoking history was found to have subcentimeter groundglass pulmonary nodules in the right lower lobe (RLL). Follow-up imaging demonstrated an increased solid component of a RLL bulla associated with mild FDG uptake on PET scan. A CT-guided biopsy revealed amyloid deposition. Case 2: 77-year-old man with a history of interstitial lung disease, asbestos exposure, prior tobacco use, and atrial fibrillation treated with amiodarone was found to have a 1.6cm RLL nodule. Follow-up imaging identified an interval increase to 2.0cm associated with moderate FDG uptake on PET scan. Transthoracic biopsy identified amyloid deposition. Discussion: Nodular pulmonary amyloidosis is a rare form of amyloidosis which may present as an enlarging pulmonary nodule with FDG avidity, raising concern for malignancy. A CT-guided biopsy is a safe way to establish a diagnosis. Recent studies have demonstrated an association between nodular pulmonary amyloidosis and marginal zone lymphomas, which warrants longitudinal follow-up for evolution to lymphoproliferative disorder.